Numerical simulation of dispersed particle-blood flow in the stenosed coronary arteries - Kaewbumrung, M.; Orankitjaroen, S.; Boonkrong, P.; Nuntadilok, B.; Wiwatanapataphee, Benchawan (Hindawi Publishing Corporation, 2018)
In this paper, a mathematical model of dispersed bioparticle-blood flow through the stenosed coronary artery under the pulsatile boundary conditions is proposed. Blood is assumed to be an incompressible non-Newtonian fluid and its ow is considered as turbulence described by the Reynolds-averaged Navier-Stokes equations. Bioparticles are assumed to be spherical shape with the same density as blood, and their translation and rotational motions are governed by Newtonian equations. Impact of particle movement on the blood velocity, the pressure distribution and the wall shear stress distribution in three different severity degree of stenosis including 25%, 50% and 75% are investigated through the numerical simulation using ANSYS 18.2 in which Eulerian description for the ow and Lagrangian description for motion of the particles. Increasing degree of senosis severity results in higher values of the pressure drop and wall shear stresses. The higher level of bioparticle motion directly varies with the pressure drop and wall shear stress. The area of coronary artery with higher density of bioparticles also presents the higher wall shear stress.